Collaborative research networks as means to increasing the productivity of African goats and sheep - Wilson, R.T.; Lebbie, S.H.B. (1990)
Discusses the need for a network approach to overcome productivity constraints in African livestock. Looks into the African Small Ruminant Research Network and discusses its intention, structure as well as training and research activities.